THE IMPACT OF SALES GROWTH, PROFITABILITY, AND ASSET STRUCTURE TOWARD CAPITAL STRUCTURE - Lie, Valensia Kristy; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2023)
This aim research is to obtain empirical evidence about the impact of sales growth, asset structure, and profitability toward capital structure. Technique sampling uses purposive sampling. The amount of sample in this research was 31 consumer goods companies that listed on the Indonesia Stock Exchange for 2018-2020. Techniques for data analysis is multiple linear regression, and processing data by using EViews. The research results concludes that sales growth has no impact toward capital structure with positive direction, asset structure has no impact toward capital structure with negative direction, and profitability has impact negatively toward capital structure.